Lightweight Implementation of the AES Encryption Algorithm for IoT Applications Constrained by Memory and Processing Power - Baneasa, Andrei; Donca, Radu; Besoiu, Sorin; Buleandra, Debora (2024 IEEE International Conference on Automation, Quality and Testing, Robotics (AQTR), 2024)
This paper explores the implementation of the AES 128 algorithm tailored for IoT devices. We have optimized the implementation to operate efficiently on some of the most cost-effective microcontrollers available. As a result, our approach offers a lightweight solution, minimizing both memory usage and required processing power. The implementation was developed for and tested on a PFS173 platform, yielding highly promising results.